Rethinking How We View Gang Members: An Examination into Affective, Behavioral, and Mental Health Predictors of UK Gang-Involved Youth. (April 2020) - Frisby-Osman, Sarah; Wood, Jane L.
Mental health difficulties, conduct problems, and emotional maladjustment predict a range of negative outcomes, and this may include gang involvement. However, few studies have examined how behavioral, mental health, socio-cognitive, and emotional factors all relate to adolescent gang involvement. This study examined 91 adolescents to compare non-gang with gang-involved youth on their conduct problems, emotional distress, guilt-proneness, anxiety and depression, and use of moral disengagement and rumination. Analyses revealed that gang-involved youth had higher levels of anxiety, depression, moral disengagement, and rumination. Gang-involved youth also had higher levels of conduct disorder and exposure to violence, but they did not differ from non-gang youth on levels of emotional distress and guilt-proneness. Discriminant function analysis further showed that conduct problems, moral disengagement, and rumination were the most important predictors of gang involvement. Discussion focuses on how intervention and prevention efforts to tackle gang involvement need to consider the mental health and behavioral needs of gang-involved youth. Further research is also needed to build an evidence base that identifies the cause/effect relationship between mental health and gang involvement to inform the best practice when tackling gang membership.